Attention-deficit/ hyperactivity disorder and the COVID-19 pandemic - Amorim,Rita (2020)
Abstract Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms is often associated with stress and anxiety. The COVID-19 pandemic forced families to adjust their lives, and the consequences on mental health are still unknown. We aim to explore how children with ADHD and their parents experienced the isolation during the COVID-19 pandemic. This is the first study focusing children with ADHD and their parents, in Portugal, during the COVID-19 outbreak. We conducted an observational, cross-sectional and analytical study. An anonymous questionnaire was designed where the impact of the quarantine in different aspects of children’s and their parent’s daily life were included. Among the 152 questionnaires obtained, 90 were related to children with ADHD and 62 to children in the control group. Children with ADHD predominantly had changes in behavior while the healthy ones mostly had no changes (p=0.035). Parents of ADHD children reported higher mean levels of stress than healthy ones and the same occurred in caregivers (p<0.001). Caregivers experienced higher levels of anxiety than their children. Parents of ADHD children stated no impact in personal development (p=0.05) and in family relations (p=0.021) against those in control group reporting mostly positive impact of the quarantine in these aspects. Our results alert not only to the importance of focusing special vulnerable groups, but also the post-pandemic surveillance of mental disorders among families.